Baby-Friendly Hospital Initiative for Neonatal Wards: impact on breastfeeding practices among preterm infants - Talita Balaminut; Sonia Semenic; Laura N. Haiek; Edilaine Giovanini Rossetto; Adriana Moraes Leite; Luciana Mara Monti Fonseca; Marialda Moreira Christoffel; Carmen Gracinda Silvan Scochi
ABSTRACT Objective: to assess breastfeeding support practices for preterm infants at two Baby-Friendly hospitals in southeastern Brazil, comparing the effect of implementing the guidelines for Baby-Friendly Hospital Initiative for Neonatal wards. Methods: a quasi-experimental study, pre- and post-intervention with control. Implementation of this initiative in the intervention hospital using Knowledge Translation. Data collection on compliance with the adapted Ten Steps, Three Guiding Principles and the Code before and after the intervention was carried out via interviews with mothers of preterm babies and professionals, unit observation and documentary analysis in the intervention and control hospitals. Intra-intergroup comparison was performed. Results: increases in global compliance with the Three Principles, Ten Steps, the Code, partial compliance with each Principle and in most Steps was greater in the intervention hospital. Conclusion: this initiative improved practices related to breastfeeding in the intervention hospital, demonstrating the potential to improve care and breastfeeding in neonatal wards.